Design of Underground Current Detection Nodes Based on ZigBee - Wei Deyu; Wu Hucheng (MATEC Web of Conferences, 2015)
At present, most current detection devices of underground power equipment in coal mines of China are equipped with the cable monitoring network. Certain problems such as difficult circuit extension and maintenance exist there. With the help of ZigBee technology, it is able to monitor the underground current of monitoring regions in coal mines safely and effectively. Major advantages include extremely low system cost, safe data transmission, flexible networking and ultra-large network capacity.